Rancang Bangun Aplikasi Analisis Kelayakan Pemberian Kredit Pada Sistem Informasi Penjualan Di UD. Adi Jaya Makmur - Rachamadho, Arliq Mushlih; Setyawan, Henry Bambang; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
UD. Adi Jaya Makmur a trading company which sale of tools and building materials. UD. Adi Jaya Makmur established in 2003 with the owner is Mr. Boedy Purwanto S.E. At 2010, that company has new a strong legal entities with obtaining IMB (Building Permit) and a Business License (Business License Trade) with number 510/22032/404.6.2/2012. During the running of the enterprise business their found variety of problems, there are many customers who late to pay the installments, amount of uncollectible, have difficulty to know the payment deadline of customer and less detailed financial reports to the company owner. From the existing problem, then created a desktop-based sales application with title “Design Build Credit Application Feasibility Analysis On Sales Information Systems at UD. Adi Jaya Makmur” wich able to give the maximum contribute to the progress of the company. Application made can also give information, corporate customers information policy, credit provision and the sale to the owner of the company.In helping companies analyzes feasibility credit provision to prospective customers using methods 5c.5c consisting of character, capacity, capital, collateral and condition of economy .To appraisement creditworthiness to prospective customers 5c, by using the method the company gave priority weights and character based on condition, appraisement vidual purposes, and the needs of companies. Based on the trial test and evaluation, note that Design Build Credit Application Feasibility Analysis On Sales Information Systems at UD. Adi Jaya Makmur with desktop-based can be a platform for business owners to advance their business. Can develop of cash and credit sales system better and easier on monitoring. And can reduce the company's losses due to the many doubtful receivables.